Irrigation Capital Requirements and Energy Costs - O'Brien, Daniel M.; Dumler, Troy J.; Rogers, Danny H. (My University, 2007)
This publication describes the economic advantages and disadvantages of irrigation in production agriculture.
MF836_2007_10
Keywords: MF836; Economics; MF